Oceanic Environmental Impact in Seaports - Nitin Agarwala; Cherdvong Saengsupavanich (Oceans, 2023)
Seaports are gateways that connect a nation to the world economy. With trade by sea increasing due to globalization, the need for the improvement and development of seaports cannot be overlooked. While the development of ports is considered essential for the economic growth and prosperity of a nation, they also result in environmental deterioration that can hurt the future of humanity. The factors that cause such deterioration are many and have been discussed and studied in some detail over the years. Of these, however, studies associated with the environmental impacts of seaports emanating from the oceanfront are limited. It is with this understanding that the current work discusses the physical and biological impacts that occur due to the oceanic environment in seaports, the existing policy provisions, and the possible ways ahead to reduce environmental deterioration and allow their sustainable operation, by means of reviewing published works.